2019
DOI: 10.1093/eurpub/ckz075
|View full text |Cite
|
Sign up to set email alerts
|

Religious service attendance, health behaviors and well-being—an outcome-wide longitudinal analysis

Abstract: Background Previous studies of relationship between religiosity, health behaviors and well-being have showed mainly positive relationships, however, are very often limited to results of associative nature and subject to unmeasured confounding. This study focused on evaluating evidence for a positive association between religious service attendance (RSA), health behaviors and well-being in a longitudinal setting and robustness of these associations to unmeasured confounding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
2
32
0
1
Order By: Relevance
“…Previous studies have found results with similarities and differences with ours. Most of them found that church attendance is negatively associated with substance use [43,[62][63][64][65]. Religious salience has been found to have less effect on substance use [62,65] or even no effect [43], which would be in accordance with our results.…”
Section: Substance Usesupporting
confidence: 92%
“…Previous studies have found results with similarities and differences with ours. Most of them found that church attendance is negatively associated with substance use [43,[62][63][64][65]. Religious salience has been found to have less effect on substance use [62,65] or even no effect [43], which would be in accordance with our results.…”
Section: Substance Usesupporting
confidence: 92%
“…An outcome-wide approach was applied, in which multiple outcomes were considered for a single exposure (VanderWeele 2017a). This approach has been theoretically argued (VanderWeele 2017a;VanderWeele et al 2020b, a) and empirically confirmed as effective in presenting temporal associations across the whole spectrum of outcomes (Białowolski et al 2019;Chen et al 2019;Chen and Vanderweele 2018;Kim et al 2020;Pawlikowski et al 2019;Steptoe and Fancourt 2020;Węziak-Białowolska et al 2018). It has the advantage of avoiding cherry-picking of significant results only, limits the risk of p-hacking (Head et al 2015;Lakens 2015) and seems to facilitate reporting of the so-called 'negative' or 'non-significant' findings, which has been already proven problematic in scientific publishing due to resistance of journal editors to publish negative results (Fanelli 2010(Fanelli , 2012Ioannidis 2005;Matosin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Community engagement, volunteering, voting in the last elections and religious service attendance (self-reported; from Wave 1) were also considered in this study because of their associations with well-being (Bloemraad and Terriquez 2016;Lim and Putnam 2010;Van-derWeele et al 2016a, b), and the protective role against financial distress (Krause 1987;Peirce et al 1996;Renneboog and Spaenjers 2012). Since there is some empirical evidence supporting their discriminatory role, the analysis accounted for labor market status (employed, looking for a job, not working), and perception of financial situation and material deprivation (worrying about expenses, food, safety, and housing) (Arber et al 2014;Green and Leeves 2013), as well as lifestyle factors (practicing a sport, drinking and smoking [Pawlikowski et al 2019]). Finally, in each regression, we controlled for the baseline values of the outcome variables (in 2017; Wave 1) to reduce confounding and the possibility of reverse causation.…”
Section: Control Variablesmentioning
confidence: 99%
“…This methodological approach to establish relationships has been successfully adopted in the fields of well-being in work life [ 25 ], households’ financial behaviors [ 116 ], religiosity [ 117 , 118 ], social psychiatry [ 115 , 119 ], and epidemiology [ 120 , 121 ], among others.…”
Section: Methodsmentioning
confidence: 99%